Synergistic effect of mixed DDA/surfactants collectors on flotation of quartz - Liu, An; Fan, Pan-Pan; Qiao, Xiao-Xiao; Li, Zhi-Hong; Wang, Huai-Fa; Fan, Min-Qiang (Minerals engineering, 2020)
•AC1201 showed a stronger synergistic ability than the other surfactants.•The flotation recovery of quartz was positively correlated with the adsorption enthalpy △adsH.•The flotation recovery of quartz was negatively correlated with the interaction parameter βm. In this study, five types of surfactants including non-ionic lipophilic surfactant Span series surfactant, non-ionic hydrophilic surfactant Tween and OP series surfactant, characteristics of both anionic and hydrophilic surfactant NaOL and triethanolamine oleate (named as OL series for short), characteristics of both cationic and hydrophilic surfactant AC1201 and AC1205 (named as AC series for short) were chosen as research subjects to investigate the relationship between the structure and synergistic ability of surfactants, focusing on the adsorption of the typical cationic collector dodecylamine (DDA) and surfactant mixture at liquid/air and solid/liquid interface to investigate the application potential of structure in the development of an effective surfactant to apply for quartz flotation. Flotation experiments, surface tension measurements, microcalorimetric experiments, interaction parameter calculation and Fourier Transform Infrared Spectroscopy (FTIR) analysis were used to analyze the characteristics of different DDA/surfactant systems and the interaction mechanism between quartz and collector mixture. The flotation results indicated that the synergistic capacity of these surfactants was in the following ranking: AC > OP > Tween > Span > OL. AC1201 showed a stronger synergistic ability than the other surfactants, accompanying with a recovery promotion over 20% compared with pure DDA. The physicochemical properties including surface activity parameters, the micelles and interfacial compositions, and interaction parameters were evaluated according to the theory of regular solutions. The surface tension and critical micelle concentration of the mixture solution decreased with the addition of the surfactant. According to the basic Rubingh equations, the interaction parameter of these surfactants was in the following ranking: OL > Span > OP > Tween > AC, indicating that the flotation recovery of quartz was negatively correlated with the interaction parameters. While there was a positive correlation between the interaction heat changes obtained from microcalorimetry and the trend from the flotation experiments. The obtained results demonstrated that it should be chosen this type of surfactant, which can be able to intensify collector adsorption at the solid/liquid interface. AC1201 has a potential for industrial application in the flotation of quartz.